Protein isoprenylation in suspension-cultured tobacco cells. - Randall, S K (1993)
Many mammalian and yeast proteins, including small ras-like GTP binding proteins, heterotrimeric G protein gamma subunits, and nuclear lamins, have been shown to be covalently linked to isoprenoid derivatives of mevalonic acid. Isoprenylation of these proteins is required for their assembly into membranes and, hence, for their biological activity. In this report, it is shown that cultured tobacco cells, when pretreated with an inhibitor of endogenous mevalonic acid synthesis (lovastatin), incorporate radioactivity from 14C-mevalonic acid into proteins. Most of these proteins are membrane associated, and many are similar in mass to mammalian ras-like GTP binding proteins and nuclear lamins. Furthermore, it is shown that tobacco cell extracts catalyze the transfer of radioactivity from 3H-farnesyl pyrophosphate and 3H-geranylgeranyl pyrophosphate to protein substrates in vitro. These studies indicate the presence of at least two distinct prenyl:protein transferases in tobacco extracts: one that utilizes farnesyl pyrophosphate and preferentially modifies a substrate protein with a CAIM carboxy terminus (farnesyl:protein transferase) and one that utilizes geranylgeranyl pyrophosphate and preferentially modifies a substrate protein with a CAIL carboxy terminus (geranylgeranyl:protein transferase type I). This work provides a basis for future work on the role of protein isoprenylation in plant cell growth, signal transduction, and membrane biogenesis.